Percutaneous instillation of physiological saline solution for the treatment of femoral pseudoaneuryms - Giurgea, Georgiana-Aura; Mlekusch, Irene; Hoke, Matthias; Carls, Alexandra; Sabeti-Sandor, Schila; Minar, Erich; Mlekusch, Wolfgang (Wiener klinische Wochenschrift, 2016)
To investigate the efficacy of para-aneurysmal saline injection for closure of postcatheterization pseudo-aneurysm (PA) at the vascular access site.
Gesehen am 16.06.2020